The Effect of Green Accounting, Corporate Social Responsibility, and Environmental, Social, and Governance on Firm Value with Profitability as a Moderating Variable in Energy Sector Companies Listed on the Indonesia Stock Exchange - Tiara Febria; Heni Safitri; Dedi Hariyanto (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze the effects of Green Accounting, Corporate Social Responsibility (CSR), and Environmental, Social, and Governance (ESG) on Firm Value, with Profitability as a moderating variable, in energy sector companies listed on the Indonesia Stock Exchange in 2024. This study employed a quantitative approach using purposive sampling. The research sample consisted of 66 energy sector companies, and the data were analyzed using Moderated Regression Analysis (MRA). The results indicate that Green Accounting has a positive and significant effect on Firm Value, whereas CSR and ESG do not have significant effects on Firm Value. Profitability has a positive and significant effect on Firm Value. Profitability strengthens the effect of Green Accounting on Firm Value, does not moderate the effect of CSR on Firm Value, and weakens the effect of ESG on Firm Value. Simultaneously, Green Accounting, CSR, ESG, Profitability, and the interaction variables have significant effects on Firm Value. The coefficient of determination of the moderation model is 41.1%, indicating that the variables in the model explain 41.1% of the variation in Firm Value, while the remaining variation is influenced by other factors outside this study.